On fuzzy semi δ - V continuity in fuzzy δ - V topological space - Halder, S.; Mukherjee, A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
New concepts of fuzzy semi δ - V and fuzzy semi δ - Λ sets were introduced in the work „On fuzzy semi δ - Λ sets and fuzzy semi δ - V sets V - 6" by the authors (J. Trip. Math. Soc., 6, 81 - 88 (2004)). It was shown that the family of all fuzzy semi δ - V sets forms a fuzzy supra topological space on X denoted by ( X, FS δ V ). The aim of this paper is to introduce the concept of fuzzy semi δ - V continuity in a fuzzy δ - V topological space. Finally, some properties, preservation theorems, etc., are studied.